Understanding Preferences for Dietary Supplements and Fortified Food during Pregnancy: A Discrete Choice Experiment. Issue 5 (13th June 2019) - Malek, Lenka; Umberger, Wendy J; Zhou, Shao Jia; Makrides, Maria; Huynh, Elisabeth
ABSTRACT: Using a discrete choice experiment, we examine pregnant women's preferences to determine the relative importance they place on product attributes when choosing between nutritionally fortified food and beverage products, and supplement tablets. The choice experiment was included in a cross-sectional web-based questionnaire completed by 857 pregnant Australian women. Latent class analysis identified four distinct consumer segments: 'Nulliparous information seekers' (42% of sample), 'Lower-income milk-lovers' (22%), 'Older multiparous tablet users' (16%), and 'Young juice-lovers' (20%). While nutrient levels were a strong driver of choice in the largest segment, over one-third of pregnant women were not influenced by levels of recommended nutrients (folate or iodine) in supplement products. Pregnancy supplements endorsed by a reputable government science agency were most appealing in three of the segments. The information gained regarding product preferences of different consumer segments can aid in targeting pregnant women and those planning pregnancy with more appropriate nutrition information, advice, and products.